2011
DOI: 10.1111/j.1742-1241.2011.02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced door-to-balloon times in acute ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention

Abstract: Institution of an on-site cardiology team-based approach in the ED significantly reduces D2B time in STEMI patients eligible for primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…In November 2006, Bradley et al [25] identified 6 strategies that were associated with reduced DTB times. Subsequently, a single page activation of the CCL by the EP was proposed as a strategy to reduce the DTB time [15,18,19,26,27,7,9,13]. Previous studies have shown that CCL activation by a single page improves DTB times [6,15,18,26,27], same as the result shown in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In November 2006, Bradley et al [25] identified 6 strategies that were associated with reduced DTB times. Subsequently, a single page activation of the CCL by the EP was proposed as a strategy to reduce the DTB time [15,18,19,26,27,7,9,13]. Previous studies have shown that CCL activation by a single page improves DTB times [6,15,18,26,27], same as the result shown in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Currently, the most widely used strategy is to activate the cardiac catheterization laboratory (CCL) through a single page. Several studies report that this system significantly reduced the DTB time [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Based on this strategy, our institution implemented a 1-call "code heart I" protocol, CCL activation through a single page by emergency physician (EP).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation the correlation of time from initial assessment to emergency department until the onset of primary angioplasty with the final outcome in patients with acute myocardial infarction was evaluated in all studies included in the review. In majority of cases, primary angioplasty was achieved initiation time of less than 90 minutes from the initial assessment, resulting in better outcomes of patients (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in case of performing culprit-vessel primary percutaneus coronary intervention before the unilateral or complete diagnostic angiography is associated with a statistically significant reduction in vascular access-to-balloon time, although the difference of 4-6 minutes is unlikely to be clinically relevant (22).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one in two AMI cases are fatal before admittance in hospital and occur more frequently within one hour of the onset of symptoms (26), whereas delayed onset of primary angioplasty by over two hours increases mortality (29). This review showed that in most cases primary angioplasty was achieved start within 90 minutes from the initial assessment, resulting in better outcomes of patients and agreement with the target time of guidelines (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation